Cyberbullying pada Film "Budi Pekerti" dalam Perspektif Al-Qur’an - Hastuti, Istrini Puji; Akhmad Rifa’i (Bahasa Indonesia, 2024)
This research examines cyberbullying in the movie “Budi Pekerti” from a Qur'anic perspective. Social media, despite its many benefits, is often misused to commit negative acts such as cyberbullying which has significant psychological and social impacts. The movie “Budi Pekerti” tells the story of Mrs. Prani and her family becoming victims of cyberbullying due to a misinterpreted viral video and facing various forms of online harassment. Bu Prani, as a teacher who upholds honesty and integrity, refuses to lie in order to save her reputation, in accordance with the teachings of the Qur'an. Analysis shows that the movie highlights the values of honesty, integrity and introspection in the face of cyberbullying, in line with the teachings of the Qur'an. Some scenes show the importance of upholding truth and justice, telling the truth, and educating with wisdom. In conclusion, “Budi Pekerti” serves as a medium of reflection and education, inviting the audience to reflect on ethical values that are often overlooked in the digital era.